Neurotrophin/Trk receptor signaling mediates C/EBPalpha, -beta and NeuroD recruitment to immediate-early gene promoters in neuronal cells and requires C/EBPs to induce immediate-early gene transcription. - Calella, A; Nerlov, C; Lopez, R; Sciarretta, C; von Bohlen und Halbach, O; Bereshchenko, O; Minichiello, L (2007)
BACKGROUND: Extracellular signaling through receptors for neurotrophins mediates diverse neuronal functions, including survival, migration and differentiation in the central nervous system, but the transcriptional targets and regulators that mediate these diverse neurotrophin functions are not well understood. RESULTS: We have identified the immediate-early (IE) genes Fos, Egr1 and Egr2 as transcriptional targets of brain derived neurotrophic factor (BDNF)/TrkB signaling in primary cortical neurons, and show that the Fos serum response element area responds to BDNF/TrkB in a manner dependent on a combined C/EBP-Ebox element. The Egr1 and Egr2 promoters contain homologous regulatory elements. We found that C/EBPalpha/beta and NeuroD formed complexes in vitro and in vivo, and were recruited to all three homologous promoter regions. C/EBPalpha and NeuroD co-operatively activated the Fos promoter in transfection assays. Genetic depletion of Trk receptors led to impaired recruitment of C/EBPs and NeuroD in vivo, and elimination of Cebpa and Cebpb alleles reduced BDNF induction of Fos, Egr1 and Egr2 in primary neurons. Finally, defective differentiation of cortical dendrites, as measured by MAP2 staining, was observed in both compound Cebp and Ntrk knockout mice. CONCLUSION: We here identify three IE genes as targets for BDNF/TrkB signaling, show that C/EBPalpha and -beta are recruited along with NeuroD to target promoters, and that C/EBPs are essential mediators of Trk signaling in cortical neurons. We show also that C/EBPs and Trks are required for cortical dendrite differentiation, consistent with Trks regulating dendritic differentiation via a C/EBP-dependent mechanism. Finally, this study indicates that BDNF induction of IE genes important for neuronal function depends on transcription factors (C/EBP, NeuroD) up-regulated during neuronal development, thereby coupling the functional competence of the neuronal cells to their differentiation.